PERBEDAAN SEDIMEN TERHADAP DAYA SERAP TEMBAGA DAN TIMBAL PADA Avicennia marina - Vita Yanuar; Isnawati Isnawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Mangroves are transitional ecosystems between land and sea where their growth is influenced by the presence of sediment, salinity, temperature, pH, DO, and other environmental factors. One of the functions of mangroves is to play a role in the absorption or binding heavy metals. The aims of this study were (1) to determine the content of heavy metals Cu and Pb in waters and soil (sediment), (2) to determine the content of heavy metals Cu and Pb in the roots and leaves of Avicennia marina , (3) to determine the effect of differences in soil texture (sediment) on the absorption of heavy metals Cu and Pb in the mangrove Avicennia marina and (4) to determine the percentage of absorption of Avicennia marina on heavy metals Cu and Pb in the coastal waters of Sungai Bakau Village. The research design was carried out using a single factor CRD (Completely Randomized Design) with differences in soil texture (sediment) on the absorption of heavy metals Cu and Pb in Avicennia marina in the coastal waters of Sungai Bakau Village. The results showed that the heavy metal content of Cu in the waters was 0.027 ppm and 0.131 ppm Pb, while in the soil (sediment) the heavy metal Cu was 1.475 ppm and the heavy metal Pb was 6.560 ppm. Cu content of heavy metal in mangrove roots was 14.223 ppm and heavy metal Pb was 1.270 ppm, while in mangrove leaves heavy metal Cu 8.607 ppm and heavy metal Pb 0.577 ppm. Differences in soil texture (sediments) have a significant effect on the absorption of heavy metals Cu and Pb in the Avicennia marina mangroves in the coastal waters of Sungai Bakau Village. The absorption percentage of Avicennia marina mangrove uptake of heavy metals Cu and Pb in the coastal waters of Sungai Bakau Village shows that uptake of heavy metal Cu is higher than uptake of heavy metal Pb.